Noah's ark - Spier, Peter; Revius, Jacobus 1586-1658. (New York Dell Dragonfly Books, 2002)
Retells in pictures how a pair of every manner of creature climbed on board Noah's ark and thereby survived the Flood.
A Caldecott Medal Book
Includes P. Spier's translation of The flood, by Jacobus Revius.
Keywords: Noah's ark; Noah's ark -- Pictorial works; Bible stories -- O.T.; Animals in the Bible